An integrated study of human and animal infectious disease in the Lake Victoria crescent small-holder crop-livestock production system, Kenya - Fèvre, Eric M.; Glanville, William A. de; Thomas, Lian F.; Cook, Elizabeth A.J.; Kariuki, S.; Wamae, C.N. (Springer, 2017)
Background The neglected zoonotic diseases (NZD) are an understudied group that are a major cause of illness throughout the developing world. In general, little is known about the prevalence and burden of NZDs in affected communities, particularly in relation to other infectious diseases with which they are often co-endemic. We describe the design and descriptive epidemiological outputs from an integrated study of human and animal zoonotic and non-zoonotic disease in a rural farming community in western Kenya. Methods This cross-sectional survey involved 2113 people, their cattle (n = 983) and pigs (n = 91). People and animals were tested for infection or exposure to a wide range of zoonotic and non-zoonotic pathogens. Prevalence estimates, with adjustment for the complex study design, were derived. Evidence for spatial clustering in exposure or infection was identified using the spatial scan statistic. Results There was a high prevalence of human parasitism in the community, particularly with hookworm (Ancylostoma duodenale or Necator americanus) (36.3% (95% CI 32.8–39.9)), Entamoeba histolytica/dispar (30.1% (95% CI 27.5–32.8)), and Plasmodium falciparum (29.4% (95% CI 26.8–32.0)). Human infection with Taenia spp. was also prevalent (19.7% (95% CI 16.7–22.7)), while exposure to other zoonotic pathogens was comparatively rarer (Brucella spp., 0.6% (95% CI 0.2–0.9); Coxiella burnetii, 2.2% (95% CI 1.5–2.9); Rift Valley fever, 0.5% (95% CI 0.2–0.8)). A low prevalence of exposure to Brucella spp. was observed in cattle (0.26% (95% CI 0–0.56). This was higher for Rift Valley fever virus (1.4% (95% CI 0.5–2.22)) and C. burnetii (10.0% (95% CI 7.7–12.2)). The prevalence of Taenia spp. cysticercosis was 53.5% (95% CI 48.7–58.3) in cattle and 17.2% (95% CI 9.1–25.3) in pigs. Mycobacterium bovis infection was found in 2.2% of cattle (95% CI 1.3–3.2), while the prevalence of infection with Mycobacterium spp. was 8.2% (95% CI 6.8–9.6) in people. Conclusion Zoonotic infections in people and animals occur in the context of a wide range of co-endemic pathogens in a rural community in western Kenya. The wide diversity of pathogens under study provides a unique opportunity to explore the distribution and determinants of infection in a multi-pathogen, multi-host system.